Studi Kelayakan Buku Ajar Bahasa Arab Berdasarkan Standar BSNP - Ahmad Fahmi Asrory; Athira Fakhriatuz Zamani; Slamet Daroini (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2022)
This study aims to analyze Arabic textbooks that are in accordance with KMA No. 183 of 2019 based on BSNP standards in terms of content/material eligibility, presentation feasibility, linguistic feasibility and graphic feasibility in class X books. This research is a descriptive qualitative approach with the type of literature study with primary data sources from class X Arabic books published by the Ministry of Religion in 2020. In this study the documentation method was used as a data collection method and combined with descriptive analysis as an analytical method. Thus, the data analysis technique used in this study is content analysis. The results of this study, the feasibility aspect of the content of the material is not appropriate in terms of the suitability of the material with KI and KD and the latest material. In the feasibility aspect, the presentation is not appropriate in supporting the presentation and learning presentation strategy. And in the aspect of language feasibility, the accuracy of language structure is still too high. However, other aspects are very appropriate and meet the standards set by the BSNP.